The Lessons of Flowshop Scheduling Research - Dudek, R. A.; Panwalkar, S. S.; Smith, M. L. (Operations Research, 1992)
This paper reviews the flowshop-sequencing research since 1954 that has been devoted to the static deterministic case in which n jobs are to be processed through a shop in which the processing times at each stage are fixed. The paper then comments on NP-completeness, the selection of criteria for optimization, and the lack of applications of this work in industry. Finally, it draws some conclusions about the possible future of sequencing research and the lessons that this area's work has to teach the rest of operations research.